The Relationship Of Insulin‑Like Growth Factor 1 With Bone Mass In Obese Female - Ardiansyah, Adek; Herawati, Lilik; Tinduh, Damayanti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aimed to analyze the relationship of insulin-like growth factor 1 with bone mass in obese female. This study used a cross sectional study method using 30 obese women aged 19-23 years, body mass index (BMI) 25-35 kg / m2, normal blood pressure, normal resting heart rate (RHR), normal hemoglobin (Hb). and fasting blood glucose (FBG) <100 mg / dL. Measurement of IGF-1 levels used the Enzym Link Immunosorbent Assay (ELISA) method. Measurement of bone mass using TANITA (Body Composition Analyzer DC3607601 (2) -1604 FA, TANITA Corporation of America, Inc., USA). The data analysis technique used the Pearson product-moment test with Statistical Package for Social Science (SPSS). The results showed that mean levels of IGF-1 (1.17 ± 0.10) ng / mL and bone mass (2.49 ± 0.06) kg (r = 0.712, P ≤ 0.001). Our findings suggest that there was a positive correlation between IGF-1 levels and bone mass